ANALISIS KINERJA KEUANGAN PADA SECTOR INDUSTRI MANUFAKTUR DALAM BIDANG MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ( PERIODE 2016–2020 ) - Mujiyani; Kristi Oktaviani (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to determine the company's performance is assessed based on the analysis of financial ratios. This study uses a descriptive type of research. The ratios used in this research are Current Ratio, Quick Ratio, Debt to Asset Ratio, Debt to Equity, Fixed Assets Turnover, Total Assets Turnover, Net Profit Margin, and Return on Assets. The results showed that the financial performance of the three companies assessed from the level of liquidity showed that they were in good condition. The solvency level shows that 2 out of 3 companies are in fairly good condition and 1 company is in a bad condition. The level of activity that the three companies show is not good. The level of activity shows that the company has not carried out the company's operations efficiently so that it is in an unfavorable condition. The level of profitability shows that the three companies are in a bad condition because they are still not able to make a profit.